Dorian Gray deve morrer: uma leitura de O retrato de Dorian Gray sob as lentes da tantopolítica e da monstruosidade - Vollet, Bruna (Universidade Federal de São Carlos, 2025)
The aim of this work is to propose an interpretation of the novel The Picture of Dorian Gray by Oscar Wilde (1891) through the lenses of the concept of thanatopolitics by Roberto Esposito (2010) and of the seven theses of monster by Jeffrey Jerome, accepting degenerate body and monster as interchangeable terms. To this end, we examine whether the narrative text distinguishes community from the degenerate body, enabling the consideration of the character Dorian Gray as a camouflaged monster. Esposito (2010), in his book Bíos, discusses the concept of thanatopolitics in conjunction with the semantics of biology, medicine, and related fields, exploring how the core of sovereign power is directed toward maintaining the health of the social body. This involves the creation of mechanisms to eliminate parts that could infect and compromise it. The cycle of life comprises four stages: regeneration, degeneration, eugenics, and genocide, all aimed at protecting health and saving the degenerate body. Furthermore, this body becomes a non-human, an other, living on the margins of society and beyond moral and legal influences, rendering it susceptible to violence imposed by sovereign power. Cohen (1996), on the other hand, explores the monster as a representation of society and culture, emphasizing its role as a tool for maintaining order and morality through the embodiment of what is different and must be feared. The monster embodies the latent fears of a given society, which may be political, sexual, racial, religious, gender-based, or otherwise. Our interpretation identifies Dorian as the degenerate body whose infection operates at a blood level, thus hidden from the community and free from condemnation. This concealment allows him to consolidate his position as a monster through this granted camouflage. His immoral and heinous actions, however, expose the monster until his inevitable downfall, as the existence of the degenerate body is unsustainable within this community. We conclude that the novel enables such interpretation and promotes strategies for the logic of thanatopolitics to unfold, promoting Dorian's salvation, as it is, the only possible outcome.
Dorian Gray must die: a reading of The picture of Dorian Gray through the lenses of tanatopoltics and monstruosity
Keywords: O retrato de Dorian Gray; Oscar Wilde; Monstruosidade; Tanatopolítica; Literatura Inglesa; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS